Towards an Equitable Sharia Economic System in the City of Tasikmalaya: The Role of Sharia Regional Regulations and Islamic Relations - Ma'mun Murod; Gunawan Santoso (BASKARA : Journal of Business and Entrepreneurship, 2023)
Sharia economic law is an important part of Islamic law. Indonesia, as a country with the largest Muslim population in the world, has enormous potential to play an optimal role in the sharia economic industry. This research is based on the phenomenon of increasing public and regional awareness of the importance of the sharia economic system in the Indonesian economy. The development of sharia regional regulations in several regions of Indonesia is part of an effort to build a sharia economic system and improve people's welfare in an equitable and just manner. The research method used is a grounded, qualitative method. This method is used to find a theory, create a new theory, and even form a new model idea that can help resolve the implementation of a just Islamic economic system. The results of the research resulted in recommendations for the best program solutions in the form of positive impact outcomes for the community, government, and business actors, namely the following activities: creating inclusive and sustainable economic growth; opening wider and more diverse business opportunities; providing an increase in the quality of life of the community; increasing public trust in the financial system; improving the nation's image; improving financial inclusion; improving economic independence; improving community welfare; and making a significant contribution to sustainable development.